Peran Ayah dalam Membangun Konsep Diri Remaja Muslim Berdasarkan Kisah-Kisah Al-Qur’an - Wafa Fauziah; Abdul Rauf Haris (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, Cianjur, indonesia, 2025)
This study examines the role of fathers in shaping the self-concept of Muslim adolescents based on stories from the Qur'an. Using a qualitative library research method, data was collected from various sources, including tafsir books, relevant books, and journals. The stories of Prophet Ibrahim, Luqman, and Prophet Ya'qub provide practical guidance for fathers in building their children's self-concept through prayer as a form of support, fostering emotional attachment, instilling faith-based values, creating spaces for dialogue and discussion, leading by example, being wise and patient in facing challenges, and surrendering to Allah regarding the outcomes of parenting. The findings reveal that fathers play a crucial role in shaping a child's self-concept across physical, moral-ethical, social, personal, and family dimensions, all grounded in Islamic values. These findings offer practical solutions to address adolescent issues, including identity crises, and emphasize the importance of Islamic values in fatherhood to support adolescents' psychosocial development. This study also highlights that parenting efforts must be accompanied by sincerity and reliance on Allah, as exemplified in the story of Prophet Nuh, which illustrates that the ultimate outcomes of parenting are entirely under Allah's will.